Equilibrium Solubility Measurement and Modeling of CO2 Absorption in Aqueous Blend of 2-(Diethyl amino) Ethanol and Ethylenediamine - Kumar S.; Padhan R.; Mondal M.K. (My University, 2025)
The equilibrium CO2 solubility in an aqueous blend of 2-(diethyl amino) ethanol (DEEA) and ethylenediamine (EDA) was performed at atmospheric preßure with the use of a laboratory scale bubbling absorber. The total concentration of amine blend solution in the range of 1.13-4.90 mol·kg-1 and the EDA mole fraction in the total amine blend in the range of 0.05-0.20 were taken. The experiments for the measurement of CO2 solubility were performed at a temperature range of 303.15-333.15 K and CO2 partial preßure range of 10.13-20.27 kPa. The analysis of CO2 in the liquid phase was accomplished by a direct titration method using HCl solution. The solubility data of CO2 in DEEA+EDA solution of the present study were compared with data available in the literature. The experimental results were applied to develop an empirical mathematical model with an average absolute deviation of 7.03% to predict the CO2 equilibrium solubility in DEEA+EDA solution within the specified range of operating conditions. In addition, the heat of absorption of CO2 in the DEEA+EDA solution was estimated by using the Gibbs-Helmholtz equation, and it was found to be-70.50 kJ mol-1 lower than that of the benchmark amine MEA. Copyright © 2020 American Chemical Society.